Approach for patch‐clamping using an upright microscope with z‐axis movable stage. Issue 6 (28th January 2022) - Perić, Mina; Bataveljić, Danijela; Bijelić, Dunja; Milićević, Katarina; Andjus, Pavle R.; Bogdanović Pristov, Jelena; Nikolić, Ljiljana
Abstract: We describe an approach for studying the physiology of single live cells using the conceptionally novel upright microscope/patch‐clamp configuration. Electrophysiology experiments typically require a microscope with the fixed stage position and the motion control of the microscope objective. Here, we demonstrate that a microscope with a z ‐axis movable stage and a fixed objective can also be efficiently used in combination with the patch‐clamp technique. We define a set of underlying principles governing the operation of this microscope/patch‐clamp configuration and demonstrate its performance in practice using cultured astrocytes, microglia, and oligodendrocytes. Experimental results show that our custom configuration provides stable recordings, has a high success rate of the whole‐cell patch‐clamp trials, can be effectively applied to study cellular physiology of glial cells, and provides comparable performance and usability to the commercially available systems. Our system can be easily replicated or adapted to suit the needs of the research groups and can be cost‐effective in reducing the investments in purchasing additional equipment. We provide step‐by‐step instructions on implementing an upright microscope with z ‐axis movable stage as a routine workhorse for patch‐clamping. Research Highlights: Approach for efficient patch‐clamping using an upright microscope with a z ‐axis movable stage. Routine study of live cell physiology. Custom microscope/patch‐clamp configuration that is cost‐effective and overcomes equipment limitations. Abstract : Custom approach for patch‐clamping using an upright microscope with a z‐axis movable stage for routine study of live cell physiology.